الميتاداتا : تحليل لاحق للانتاج الفکرى - رحاب محمد ابو الغار (المجلة الدولية لعلوم المكتبات والمعلومات)
Meta-analysis is considered a research style in the field of libraries andinformation, one of the efforts of registering Literature. this style is remarkablewith three features that cannot stand without which fusion (collecting orintegration) between previous results of the study and summarizing these results,meeting and comparing them with each other, using some statistical methods inthis summary to perform bibliometric analysis, of previous studies. this study triesto apply Meta-analysis style on one of the topics " metadata" with analyzing itwith qualitative, quantative, time and linguistic analysis and clarifying scientifictrends of the topic, in this study, the researcher tried to analysis previous studiesaccording to objective elements of the study, this is to recognize common andgeneral results that studies of this topic had reached to.The intellectual production that dealt with the subject of metadata in itsbranches, which amounted to 61 studies, was presented and analyzed to identifyits objective, temporal, qualitative, formal and syntactic features andcharacteristics, and the methodology used.The most important recommendations, proposals or future researchdirections regarding metadata are the following: Conducting some applied studies dealing with metadata of museumgroups and metadata of multimedia. Study the quality of the metadata of media, especially news websites, onthe Internet. Conducting many studies on the topic of "Big Metadata" and "LinkedMetadata" Methods used to describe metadata between Arab and foreign indexes(that use correlated data): a comparative study. Future directions for describing metadata of indexes in the environment oflinked data: an exploratory study. Here, the researcher did not intend toaddress metadata of indexes because it was dealt with by some studies,but to explore the relationship of interrelated data in managing andcreating metadata.